SAG therapy restores bone growth and reduces enchondroma incidence in a model of skeletal chondrodysplasias caused by Ihh deficiency - Xinhua Li (Elsevier, 2021)
Inactivation mutations in the Indian hedgehog (Ihh) gene in humans cause numerous skeletal chondrodysplasias, including acrocapitofemoral dysplasia, brachydactyly type A1, and human short stature. The lack of an appropriate human-relevant model to accurately represent these chondrodysplasias has hampered the identification of clinically effective treatments. Here, we established a mouse model of human skeletal dysplasia induced by Ihh gene mutations via ablation of Ihh in Aggrecan-positive (Acan+) cells using Aggrecan (Acan)-creERT transgenic mice. Smoothen agonist (SAG) promoted Hh activity and rescued chondrocyte proliferation and differentiation by stimulating smoothened trafficking to the cilium in Ihh-silenced cells. SAG treatment corrected mouse stature and significantly decreased mortality without evidence of toxicity. Moreover, Ihh ablation in Acan+ cells produced enchondroma-like tissues near the growth plates that were significantly reduced by SAG treatment. These results demonstrated that SAG effectively treats skeletal dysplasia caused by Ihh gene mutations in a mouse model, suggesting that SAG may represent a potential drug for the treatment of these diseases and/or enchondromas.